Concretization of Online Accreditation to Improve the Quality of Digital Technology-Based Education Services in the New Normal Era - Martinelli, Ida; Khairiah, Nalil (PERSPEKTIF, 2024)
This article aims to investigate the implementation of accreditation to enhance the quality of technology-based education services in the new normal era. The primary focus of the research is on the concrete application of online accreditation based on digital technology in the field, associated with the improvement of educational service quality. The research approach utilizes school accreditation guidelines as a reference, collecting data through interviews and document analysis, which is then qualitatively analyzed. The findings indicate that the successful implementation of online accreditation is contingent upon schools providing facilities, infrastructure, and human resources professionals in using digital technology in educational services. Furthermore, the quality of educational services is reflected in the school's output, particularly in the superior quality of graduates from accredited A-level schools compared to non-accredited ones. By employing digital technology in the accreditation process, schools face the challenge of cultivating habits of using digital technology in their operational procedures. Ultimately, this positively contributes to the overall improvement of the quality of educational services. With efficient administrative management and well-managed learning processes, technology-based accreditation encourages schools to continually adapt and enhance themselves to achieve optimal educational service quality.